2018
DOI: 10.1002/jclp.22564
|View full text |Cite
|
Sign up to set email alerts
|

Examination of interoception along the suicidality continuum

Abstract: These findings suggest that interoception may be impaired in those with a history of suicidal thoughts and behaviors. Longitudinal designs are needed to parse apart the interplay of these variables and directionality of these relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 73 publications
11
36
0
Order By: Relevance
“…For researchers, distilling particular elements shared between autism and other conditions associated with NSSI would be valuable. Poor interoceptive awareness, for instance, is shared by people with eating disorders [110], autistic people [111], and self-harmers and people who report suicide ideation or attempts [112]. In this study, suicide-attempters were less likely to ignore or distract themselves from painful sensations and were less able to regulate distress by paying attention to bodily sensations [112].…”
Section: Limitations and Directions For Future Studymentioning
confidence: 59%
See 1 more Smart Citation
“…For researchers, distilling particular elements shared between autism and other conditions associated with NSSI would be valuable. Poor interoceptive awareness, for instance, is shared by people with eating disorders [110], autistic people [111], and self-harmers and people who report suicide ideation or attempts [112]. In this study, suicide-attempters were less likely to ignore or distract themselves from painful sensations and were less able to regulate distress by paying attention to bodily sensations [112].…”
Section: Limitations and Directions For Future Studymentioning
confidence: 59%
“…Poor interoceptive awareness, for instance, is shared by people with eating disorders [110], autistic people [111], and self-harmers and people who report suicide ideation or attempts [112]. In this study, suicide-attempters were less likely to ignore or distract themselves from painful sensations and were less able to regulate distress by paying attention to bodily sensations [112]. Interoceptive "disconnect" with the experience of pain would, theoretically, make self-harmers capable of severely hurting the body much as an object; that they exhibit both higher tolerance for pain and decreased fear of pain is consistent with the central role that both play in acquired capability for suicide [113].…”
Section: Limitations and Directions For Future Studymentioning
confidence: 99%
“…Currently, few self‐report measures with strong psychometric properties exist. Although the MAIA appears to be the most comprehensive, some subscales have not demonstrated good reliability (Mehling et al, ), and not all subscales relate to SITBs (Rogers, Hagan, & Joiner, ). Additionally, self‐report measures are prone to their own limitations, which could be exacerbated among individuals who have trouble perceiving their physiological sensations.…”
Section: Discussionmentioning
confidence: 99%
“…Forcano et al [16] reported that women with bulimia nervosa who had attempted suicide had yet greater interoceptive sensibility deficits than those who had not attempted. A more recent study [17] reported that people with lifetime suicide attempts tend to distract themselves from bodily sensations, and those with lifetime suicide ideation reported increased worry about bodily sensations. There was a lack of trust of bodily sensations for participants across the suicidal continuum.…”
Section: Introductionmentioning
confidence: 98%